2021
DOI: 10.3390/nu13082660
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Probiotic NVP-1704 on Mental Health and Sleep in Healthy Adults: An 8-Week Randomized, Double-Blind, Placebo-Controlled Trial

Abstract: The human gut microbiome is closely linked to mental health and sleep. We aimed to verify the efficacy and safety of probiotic NVP-1704, a mixture of Lactobacillus reuteri NK33 and Bifidobacterium adolescentis NK98, in improving stress, depression, anxiety, and sleep disturbances, along with the measurement of some blood biomarkers. A total of 156 healthy adults with subclinical symptoms of depression, anxiety, and insomnia were retrospectively registered and randomly assigned to receive either NVP-1704 (n = 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
68
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 75 publications
(76 citation statements)
references
References 49 publications
(55 reference statements)
5
68
0
3
Order By: Relevance
“…Lactobacillus reuteri NK33 and Bifidobacterium adolescentis NK98 mitigate stress-induced depression and colitis in mice by the attenuation of gut dysbiosis [ 16 , 20 ]. NVP1704, a combination of NK33 and NK98, alleviates depressive and anxious symptoms in individuals with anxiety, depression, and insomnia [ 24 ]. In addition, anti-inflammatory drugs mitigate gut inflammation and depression [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lactobacillus reuteri NK33 and Bifidobacterium adolescentis NK98 mitigate stress-induced depression and colitis in mice by the attenuation of gut dysbiosis [ 16 , 20 ]. NVP1704, a combination of NK33 and NK98, alleviates depressive and anxious symptoms in individuals with anxiety, depression, and insomnia [ 24 ]. In addition, anti-inflammatory drugs mitigate gut inflammation and depression [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…As such, a pilot study in patients with chronic primary insomnia suggested that the consumption of L. plantarum PS128 could reduce the events of waking up at NREM3 sleep, compared with the placebo group (Ho et al, 2021). Another study, in stressed adults with symptoms of depression or anxiety, reported that Limosilactobacillus reuteri NK33 and Bifidobacterium adolescentis NK98 tended to reduce the overall PSQI scores after eight weeks of consumption, compared with the placebo group (P=0.068) (Lee et al, 2021). In a singlearm study where highly stressed IT workers consumed L. plantarum PS128 daily for eight weeks, both stress and insomnia symptoms were reduced at week eight compared with baseline measurements (Wu et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…[145] A probiotic mix improved sleep quality. [146] Gut microbiome status including altered metabolism affects sleep. [147] Probiotic supplementation improved sleep among postoperative cancer patients.…”
Section: Details Reference(s)mentioning
confidence: 99%